Management accounting change and the role of controller in different stages of enterprise life cycle : Case study on a large manufacturing company - Hämäläinen, Miikka (My University, 2019)
This thesis examines whether the life-cycle of an organization affects the role of the management accountant and what elements characterize this possible change. The study also explores the various factors that impact the work and role change of modern accountants. The study is qualitative in nature and is based on a field study conducted at the case organization between 2013 and 2017. The study focused on the effects of the life-cycle on management accountants during turbulent times that the case organi-zation went through during the time of the study. Empirical evidence of the research consist of discussions, meeting observations, internal documents and a questionnaire that was sent out to the finance community of the case company. The results suggest that certain dichotomy exists with modern rehearsing of the profession; we conclude that the changes in the life cycle of the company provides opportunities to those man-agement accountants that are willing to take the necessary leap of faith in terms of new ways of working and adapting new roles and responsibilities. Consequently, the find-ings indicate that the role of the management accountant is affected by the changes in organizational life cycle. However, the changes in the role seem to take place indirect-ly in relation to the life cycle. The change in life cycle stage might trigger other changes, such as changes in top management, organizational restructurings or some form of M&A actions. These changes then trigger the need to revisit the roles of man-agement accountants. Based on the empirical findings this study suggests that man-agement accountants are moving towards more strategic and business partnership based role. The findings of the study are subject to some limitations and further re-search for instance on the new, emerging roles of MAs is encouraged.
Keywords: Management accounting change, enterprise life-cycle, role of controller, case-study